1979
DOI: 10.1007/bf00389701
|View full text |Cite
|
Sign up to set email alerts
|

Hajdu-Cheney syndrome

Abstract: Hadjdu-Cheney syndrome is a rare type of syndrome characterized by acro-osteolysis, dolichocephaly with multiple Wormian bones, absence of frontal sinuses and joint laxity. A case of this syndrome is presented. A histological study of the osteolytic lesion revealed destruction characterized by microfractures with a poor reparative process. It is postulated that an abnormality of osteoblast or osteoid function is the pathogenesis of this syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

1991
1991
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 8 publications
1
14
0
Order By: Relevance
“…However, Notch2 +/HCS mice did not develop acro‐osteolyses, a specific hallmark of HCS. Because it has been suggested that the underlying mechanisms causing acro‐osteolyses involve external stimuli, such as microdamages or inflammatory events, it is conceivable to speculate that the mice analyzed in our study did not experience sufficient mechanical loading and abrasion or pathogen exposure on their phalanges to trigger development of this symptom. In addition, we observed no incidences of renal cysts; however, this symptom is reported to occur only in 18% of human cases.…”
Section: Discussionmentioning
confidence: 96%
“…However, Notch2 +/HCS mice did not develop acro‐osteolyses, a specific hallmark of HCS. Because it has been suggested that the underlying mechanisms causing acro‐osteolyses involve external stimuli, such as microdamages or inflammatory events, it is conceivable to speculate that the mice analyzed in our study did not experience sufficient mechanical loading and abrasion or pathogen exposure on their phalanges to trigger development of this symptom. In addition, we observed no incidences of renal cysts; however, this symptom is reported to occur only in 18% of human cases.…”
Section: Discussionmentioning
confidence: 96%
“…Besides the skeletal lesions, the clinical course is determined by the development of neurological complications (5)(6)(7)(8)(9) due to anomalies of the craniovertebral junction, which may cause basiliar invagination. Fortunately our patient did not have respective complications during followup until the age of 39 years.…”
Section: Discussionmentioning
confidence: 99%
“…H AJDU-CHENEY SYNDROME (hereditary osteodysplasia with acro-osteolysis) is a rare disorder characterized by the typical findings of acro-osteolysis, brachydactyly, a distinctive facies with micrognathia, early loss of teeth, and short stature. The syndrome occurs sporadically (1)(2)(3)(4)(5)(6)(7)(8)(9) or familial with autosomal dominant inheritance. (10)(11)(12)(13)(14)(15) Acroosteolysis usually develops in late childhood in the distal phalanges of the fingers and, less frequently, of the toes.…”
Section: Introductionmentioning
confidence: 99%
“…It has also been shown to have both oncogenic and tumor suppressor roles in different types of cancers . Mutations in the Notch2 gene can cause Alagille and Hajdu‐Cheney syndromes, two autosomal‐dominant genetic conditions that affect skeletal, cardiovascular, neural, and gastrointestinal system development . An association between the mutation of the Notch4 gene and susceptibility to schizophrenia has been described .…”
Section: Introductionmentioning
confidence: 99%